Total Thyroidectomy Without Sternotomy for a Massive Retrosternal Goiter with Simultaneous Occurrence of Two Thyroid Carcinomas: Outcomes and Surgical Approach - Alkhelaif , Rana; Almajed, Ebtesam; Ghulam , Raghad; Algabr, Ghadah Abdulrahman; Alrasheedi, Saud; Alzahrani, Abdulrahman; Alqahtani, Adel (Brazilian Journal of Case Reports, 2025)
Retrosternal goiters often lead to compressive symptoms such as dyspnea, dysphagia, and neck fullness, and pose significant surgical challenges. The standard treatment is total thyroidectomy, though the need for sternotomy depends on the size and extension of the goiter. We present a case of a 51-year-old woman with a progressively enlarging anterior neck mass. Imaging revealed markedly enlarged thyroid lobes with retrosternal extension, causing tracheal deviation and narrowing. CT showed heterogeneous nodules with cystic, necrotic, and calcified components; the lobes measured 13×7×8.2 cm and 8.3×4.6×5.1 cm. No lymphadenopathy was noted. She underwent total thyroidectomy via a 6 cm collar incision, using careful dissection and manipulation despite deep intrathoracic extension. Gross pathology revealed intact capsules, and histopathology showed a thyroid collision carcinoma: a minimally invasive follicular carcinoma (pT3a, pN0a) on the left and an encapsulated angioinvasive oncocytic carcinoma (pT1b, pN0a) on the right. Postoperatively, the patient experienced transient hypoparathyroidism, which resolved with calcium supplements. This case highlights the feasibility of performing total thyroidectomy for giant retrosternal goiters without sternotomy, even when the goiter extends to the lung hilum. Avoiding sternotomy minimizes perioperative risks and recovery times. Histopathology revealed synchronous differentiated carcinomas of follicular origin, highlighting the importance of complete resection in retrosternal goiters.